Post-Assault Health Care for Sexual Assault Survivors During COVID-19: A Mixed Methods Analysis of Service Rates in a Predominately African American Community. Issue 1 (January 2023) - Campbell, Rebecca; Javorka, McKenzie; Engleton, Jasmine; Goodman-Williams, Rachael; Gregory, Katie
This study examined how the COVID-19 pandemic affected sexual assault healthcare services in a predominately African American U.S. city. In mixed methods research design, we used quantitative interrupted time series modeling to evaluate changes in service rates for three core post-assault healthcare services—medical forensic exams (MFEs), medical advocacy MFE accompaniment, and counseling—from January 2019 through June 2021. We also conducted qualitative interviews with 12 sexual assault advocates to understand how their clients were impacted by COVID and how their agency adapted services to respond to the needs of their community. Both the quantitative and qualitative data revealed marked disruptions in service provision. The number of MFEs, medical advocacy accompaniments, and counseling sessions significantly decreased during the pandemic's initial surge, and survivors feared seeking hospital-based health care due to concerns that they might contract COVID-19 in hospital emergency departments. The number of MFEs performed by program staff did not return to pre-pandemic levels during this study's observation period, but the number of medical advocacy accompaniments and counseling sessions did significantly rebound. Counseling services eventually exceeded pre-pandemic levels as agency staff supported clients with both assault- and COVID-related trauma and loss. These results underscore the need for community-based sexual assault healthcare services, so that if public health emergencies limit the availability, accessibility, and safety of hospital emergency department care, sexual assault survivors have other settings for obtaining post-assault health care.